John S. Bell on the foundations of quantum mechanics - editors; M. Bell; K. Gottfried; M. Veltman
This volume is the most complete collection of John S. Bell's research papers, review articles and lecture notes on the foundations of quantum mechanics. Some of this material has hitherto been difficult to access. The book also appears in a paperback edition, aimed at students and young researchers. This volume should be useful to researchers in the foundations and applications of quantum mechanics